Double blind trial of repeated treatment with transdermal nicotine for relapsed smokers. - Gourlay, S. G. (BMJ Group, 1995)
OBJECTIVE--To assess the efficacy and safety of a repeat course of treatment with transdermal nicotine for cessation of smoking in a brief intervention setting. STUDY DESIGN--Randomised, double blind, placebo controlled trial with follow up for 26 weeks. SUBJECTS--629 smokers who had unsuccessfully attempted to stop smoking by using active transdermal nicotine and brief behavioural counselling. Smokers were motivated to quit smoking for a second time and smoked > or = 15 cigarettes a day. INTERVENTIONS--Twelve weeks' treatment with active transdermal nicotine patches or placebo and brief counselling at monthly visits. MAIN OUTCOME MEASURE--Sustained smoking cessation for the 28 days before the visit at week 12 verified by expired carbon monoxide concentrations. RESULTS--At 12 weeks 21/315 (6.7%) subjects allocated to active treatment had stopped smoking compared with 6/314 (1.9%) allocated to placebo (absolute difference 4.7%; 95% confidence interval 1.6% to 7.9%; P = 0.003). At 26 weeks the rates were 20/315 (6.4%) and 8/314 (2.6%) (3.8%; 0.6% to 7.0%; P = 0.021). Difficulty in sleeping was reported by 43/179 (24.0%) on active treatment and 19/143 (13.3%) on placebo (P = 0.015). Severe reactions at the site of application were rare (6/322; 1.9%). CONCLUSIONS--Repeated treatment with transdermal nicotine together with brief counselling can improve the low success rates of smoking cessation in recently relapsed, moderate to heavy smokers. Questions remain about whether more intensive interventions or higher doses of nicotine could be more effective. The likelihood of severe reactions at the site of application with repeated treatment is low.